Incomplete democracy : political democratization in Chile and Latin America - Garretón Merino, Manuel A. (Manuel Antonio) (Latin America in translation/en traducción/em tradução., 2003)
Sociologist Manuel Antonio Garreton discusses contemporary challenges to democratization in Latin America in this work. He pays particular attention to the example of Chile, analysing the country's return to democracy and its hopes for continued prosperity following the 1973 coup.